Return migration and real estate projects: philanthropy or speculation? The examples of Le Locle and Locarno (Switzerland), from the mid-19th century to the 1910s - Lorenzetti, Luigi (Dve domovini, 2025)
The migration experiences of the past often generated financial flows linked to remittances or capital repatriation, whose main market was the private construction sector. It usually consisted of the construction of dwellings intended to complete the conservative project of the return to the homeland and represent the success of the personal career. The article draws on two real estate projects realized in two Swiss towns to show how, for two figures with a migration background from the mid-19th century onwards, the construction sector represented an entrepreneurial strategy based on a different balance between philanthropic idealism and speculative logic.
Keywords: dobrodelnost; enterpreneurship; migracije; migration; philanthrophy; podjetništvo; povratništvo; return migration